The effect of cigarette taxes during pregnancy on educational outcomes of the next generation - Sonja Settele; Ewijk van Reyn (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
Smoking during pregnancy is most common among women with a low socioeconomic status and is negatively associated with important infant health measures such as birth weight. Cigarette taxes decrease smoking amongst pregnant women, thereby leading to improved birth outcomes. In this paper we investigate whether increasing cigarette taxes can reduce the intergenerational transmission of a low socioeconomic status by reducing smoking rates among pregnant women with low educational attainment. In a first step, we exploit variation in cigarette taxes across U.S. states over time to show that increasing cigarette taxes leads to improvements in the health of newborns which are larger for babies of low educated mothers. In a second step, we look at subsequent educational success of 16-year-olds measured by grade retention and school enrollment in a large sample of adolescents. We find that increasing cigarette taxes improves the outcomes of children from a low socioeconomic background, but find no effects among children from a higher socioeconomic background. Our findings therefore suggest that cigarette taxes can be an effective policy instrument for mitigating the propagation of a low socioeconomic status from one generation to the next.
Keywords: I12; I14; I24; 330; Early Life; Tobacco Taxes; Socioeconomic Inequalities